A Scientific Analysis of the Concept of Love in "Almost Heaven" by Judith Mcnaught and "Days Gone by" by Abdulla Qadiriy (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The concept is the object of study of both cognitive linguistics and linguoculturology. The concept is a mental structure that is a basic unit of the human thinking code that has a relatively ordered internal structure, a complex, encoded information about the subject or event that is reflected and expressed as a result of cognitive activity.